The imbalance of self-reported wanting and liking is associated with the degree of attentional bias toward smoking-related stimuli in low nicotine dependence smokers - File, Domonkos; Petro, Bela; Kojouharova, Petia; Kővári, Lili; Gaál, Zsófia Anna; Demetrovics, Zsolt; Czigler, István (Frontiers in Psychology, 2024)
Background and aims The Incentive Sensitization Theory (IST) offers a comprehensive framework that explains how attentional mechanisms contribute to the maintenance and relapse of addictive behavior. However, the extent to which the underlying neuropsychological mechanisms are consciously accessible for report remains unknown. Thus, the aim of this study was to investigate the association between self-reported wanting and liking among smokers and its relationship with detecting changes in smoking-related stimuli. Design An online experiment was designed deploying a flicker paradigm with neutral and smoking-related changes, completed by 422 individuals (mean age = 29.1 years, 214 non-smokers, 123 current smokers, and 85 former smokers). Additionally, the Fagerström Test for Cigarette Dependence and the Imaginative Wanting and Liking Questionnaire were administered. Findings Consistent with prior research findings, smokers exhibited faster detection of smoking-related changes compared to non-smokers, while former smokers displayed an intermediate level of attentional bias, falling between the levels observed in smokers and non-smokers. Further, higher levels of nicotine dependence were associated with a greater discrepancy between self-reported wanting and liking, which was associated with better change detection performance for high salience smoking-related stimuli in smokers. Conclusion These findings support the predictions of IST and support the notion that attentional bias might develops early in the course of nicotine addiction. Furthermore, the results indicate that the underlying cognitive mechanisms might be partially within conscious awareness, which opens up potential avenues for research design, treatment, and interventions.